THE EFFECTIVENESS OF COASTAL AREA MANAGEMENT PROGRAMS IN IMPROVING THE ECONOMICS OF THE ESSANG DISTRICT OF TALAUD ISLANDS - WADO, MIRANDA; LALOMA, ALDEN; RURU, JOORIE MARHAEN (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: Coastal and marine areas are areas that have potential and prospective resources for a region if themanaged optimally. This is a challenge for a region in managing resources in a sustainable manner toencourage the acceleration of regional development. As a very atrategic area, the coastal area is a zone ofallotment of various human activities both social, cultural, economic, industrial and utilization of naturalresources directly.High dependence on marine resources has led to massive exploitation. This is what happens with the resourcesof coral reefs which are the most important ecosystems in the coastal and marine areas. The main threats tocoral reefs are overfishing, destructive fishing practices, sedimentation and pollution from the land. Burke etal, (2002) suggests that human activity is currently estimated to threaten 88 percent of Southeast Asian reefs,threatening important biological and economic values for society. About 50 percent of the coral reefs that arethreatened, are at a high or very high level of vulnerability. Only 12 percent of them are at a low threat level.Result of researchconducted through data collection obtained through observation, dokuments and interviews.The results of this study indicate that the process of coastal are management goes well. Thanks to thecooperation between the village head and the village apparatus and the villagers so that they can producemaximum results. The basis and reference in measuring the effectiveness of coastal area management programin improving the economics of Maririk village community of Essang district of Talaud islands is in theregulation of Law Number 27 year 2007.Keywords: Peis Area Management